Dynamically Accumulating Homologous Recombination Deficiency Score Served as an Important Prognosis Factor in High-Grade Serous Ovarian Cancer - Su, Rongjia; Liu, Yuan; Wu, Xiaomei; Xiang, Jiangdong; Xi, Xiaowei (Frontiers in Molecular Biosciences, 2021)
Background: Homologous recombination (HR) pathway defects in cancers induced abrogation of cell-cycle checkpoints resulting the accumulation of DNA damage, mitotic catastrophe and cell death. Cancers with BRCA1/2 loss and other accumulation of similar genomic scars resulting in HRD displayed increased sensitivity to chemotherapy. Our study aimed to explore HRD score genetic mechanisms and subsequent clinical outcomes in human cancers especially ovarian cancer. Methods: We analyzed TCGA data of HRD score in 33 cancer types and evaluated HRD score distribution and difference among tumor stages and between primary and recurrent tumor tissues. Weighted Gene Co-Expression Network Analysis (WGCNA) was performed to identify highly correlated genes representing essential modules contributing to HRD score and distinguish the hub genes and significant pathways. We verified HRD status predicting role in patients overall survival (OS) with univariate and multivariate Cox regression analysis and built the predicting model for patient survival. Results: We found that HRD score increased with the rising of tumor stage except for stage IV. HRD score tended to grow up higher in recurrent tumor tissue than in primary counterpart (p=0.083). We constructed 15 co-expression modules with WGCNA, identified co-expressed genes and pathways impacting HRD score and concluded that HRD score was tightly associated with tumor cells replication and proliferation. Combined HRD score ≥42 was associated with shorter OS in altogether 33 cancer types (HR=1.010, 95%CI: 1.008-1.011, p <0.001). However, in ovarian cancer which ranked the highest HRD score among cancers, HRD ≥42 cohort was significantly associated with longer OS (HR=0.99, 95%CI:0.98-0.99, p<0.0001). We also built a predicting model for the 3-year and 5-year survival in HGSC patients. Conclusion: Quantitative HRD score representing the accumulated genomic scars was dynamically increasing in proliferating tumor cells, since HRD score was tightly correlated to tumor cell division and replication. We highlighted HRD score biomarker role in prognosis prediction of ovarian cancer.